Natural history of inflammation and impaired autophagy in children with Gaucher disease identified by newborn screening - V. Gragnaniello; D. Gueraldi; A. Saracini; D. Velasquez Rivas; C. Cazzorla; L. Salviati; A.B. Burlina (Molecular Genetics and Metabolism Reports)
Introduction: Gaucher disease is a lysosomal storage disease due to deficiency of glucocerebrosidase, leading to the accumulation of glucosylceramide, particularly in macrophages. In addition to storage, secondary abnormalities such as inflammation, cellular stress, and impaired autophagy may contribute to the disease pathogenesis. The onset and course of progression of these secondary abnormalities remains unclear. Owing to the increasingly widespread newborn screening programs, diagnosis can be made at a presymptomatic stage. Understanding the early natural course of the disease is important for optimal monitoring and management of such at-risk individuals.The aim of our study is to investigate secondary abnormalities in very young children with type 1 Gaucher disease identified through neonatal screening. Materials and methods: We enrolled five children (<4 years old) with type I Gaucher disease in a presymptomatic stage and not receiving therapy. We assessed plasma cytokine profiles (TNFα, IL1β, and IL6 by ELISA), activation of pro-inflammatory p38 mitogen-activated protein kinase (MAPK) and the abundance of LC3-II as indicator of autophagic flux, by immunoblotting. Results: All subjects exhibited elevated TNFα (mean 21.74 μmol/L, SD 37.48, range 2.37–88.72 μmol/L). The other cytokines analyzed were within normal range. Cellular stress (activation of p38) was present in the child with higher glucosylsphingosine (GluSph) accumulation. Additionally, all subjects showed a significant reduction in LC3-II (mean 88 %, SD 9 %, range 77–98 %), indicating reduced autophagic flux. Discussion: We have identified the presence of inflammation with inhibition of autophagic flux in presymptomatic young children with a genetically confirmed high-risk of developing Gaucher disease. These findings contribute insights into the early course of Gaucher disease and support the management of at-risk individuals identified by newborn screening. Therapeutic interventions including specific enzyme replacement or other means to address inflammation or autophagy could delay or prevent the onset of symptomatic disease and consequential disability. Further clinical studies are warranted to explore these possibilities.